Comprehensive Physiology 2019
DOI: 10.1002/cphy.c180032
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA: Genomics and Relevance to Physiology

Abstract: The mammalian cell expresses thousands of long noncoding RNAs (lncRNAs) that are longer than 200 nucleotides but do not encode any protein. lncRNAs can change the expression of protein‐coding genes through both cis and trans mechanisms, including imprinting and other types of transcriptional regulation, and posttranscriptional regulation including serving as molecular sponges. Deep sequencing, coupled with analysis of sequence characteristics, is the primary meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 142 publications
0
20
0
Order By: Relevance
“…Of note, a number of the guide snoRNA-hosting genes in humans are spliced, polyadenylated lncRNAs that are dynamically regulated during cell proliferation, differentiation, and apoptosis [16][17][18]. These genes also exhibit cell-and tissue-specific expression patterns [19][20][21]. snoRNA host genes are believed to be required for the specific recruitment of snoRNPs that influence modification and eventually re-enforce cell fate decisions to ensure a step-wise developmental transition [22].…”
Section: Introductionmentioning
confidence: 99%
“…Of note, a number of the guide snoRNA-hosting genes in humans are spliced, polyadenylated lncRNAs that are dynamically regulated during cell proliferation, differentiation, and apoptosis [16][17][18]. These genes also exhibit cell-and tissue-specific expression patterns [19][20][21]. snoRNA host genes are believed to be required for the specific recruitment of snoRNPs that influence modification and eventually re-enforce cell fate decisions to ensure a step-wise developmental transition [22].…”
Section: Introductionmentioning
confidence: 99%
“…All eligible literature included in our meta-analysis met the following criteria: (1) The expression of the lncRNA TUG1 was measured in human tumors, and patients were grouped according to the expression levels of TUG1. (2) Assessment of the relationship between TUG1 expression and overall survival (OS), progression-free survival (PFS), disease-free survival (DFS), recurrent-free survival (RFS), event-free survival (EFS), or clinicalpathological parameters such as tumor differentiation, tumor stage, and metastasis.…”
Section: Study Selectionmentioning
confidence: 99%
“…Long noncoding RNAs (lncRNAs) are an emerging class of vital regulators participating in various biological functions and disease processes to different degrees [1,2]. Nextgeneration sequencing has revealed that specific lncRNAs are mutated or aberrantly expressed in cancers, and the specific role of lncRNAs in different tumors is yet to be annotated [3].…”
Section: Introductionmentioning
confidence: 99%
“…The estimated number of lncRNA genes in the human genome is 16,000 (1). According to the relative position of the lncRNA and protein gene in the genome, lncRNAs are identified into five types: sense lncRNAs, antisense lncRNAs, bidirectional lncRNAs, intronic lncRNAs, and intergenic lncRNAs (also termed long intergenic non-coding RNAs [lincRNAs]) (2). Recently, lncRNAs have been demonstrated to exert a crucial effect on a variety of biological activities by affecting gene expression in different types of cancer (3,4).…”
Section: Introductionmentioning
confidence: 99%